Hegemonic Shifts: The Latest from the Walls of Northern Ireland - Tony Crowley (Estudios Irlandeses, 2015)
This essay considers the changes that have taken place in the murals of Northern Ireland over the past decade or so. It will be argued that although there have been important developments in the murals that reflect the consolidation of ‘peace’ during this period, the walls also tell a different story.  It will be shown that, perhaps predictably, given the paralysis and stagnation that have characterised the power-sharing arrangements, and the disillusionment, cynicism and bitterness towards the political settlement which is now evident, a number of murals offer representations that indicate the growth of tendencies that present latent but real dangers.